Natural rights on the book "Silent Springer" Critical Review of Ecological Citizenship - Dewantara, Jagad Aditya (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2024)
Rachel Carson's book "Silent Spring" is often credited with kicking off the modern environmental protection movement. In the book, Carson details the destructive effects that synthetic pesticides, particularly D.D.T., can have on ecosystems and human health. This book, first released in September of 1962, coincidentally served as a gathering place for those involved in the environmental movement. Carson argues in his book that pesticides such as D.D.T. eliminate bugs and wreck the food chain and the natural environment. It poses a risk to the populations of birds and fish and might make youngsters more susceptible to illness (Carson, 2002).Carson further said that public authorities blindly accepted the marketing promises made by the chemical business without giving the claims proper attention. He accused the chemical industry of disseminating deception. Carson started working on environmental conservation concerns in the late 1950s, focusing primarily on problems relating to synthetic pesticides. His study led to the production of the film "Silent Spring," which raised people's awareness of environmental issues in American culture. The book was met with considerable criticism from chemical firms. However, it managed to influence public opinion, which led to a reversal in pesticide policy in the United States, including a nationwide ban on the use of D.D.T. for agricultural purposes. It ultimately led to the formation of the Environmental Protection Agency (EPA). Because of Carson's work, there has been a substantial shift in how individuals and governments think about the environment and humans' role in destroying it. The book also ignited a discussion about the regulation of the use of pesticides and responsibility for nature. As a result, it became one of the most essential works in the history of environmental conservation movements and motivated efforts to conserve wildlife and maintain the balance of ecosystems. In addition, the book became one of the most influential works in the history of environmental conservation movements.